Understanding Muslim Identity - Adis Duderjia (International Institute of Islamic Thought, 2010)
Gabrielle Marranci seeks to shift the analyses of “Islamic fundamentalism/ radicalism” discourses away from those focusing on cultural and political essentialism, scripturalism, and social determinism and toward that of exploring the dynamics of radicalization by examining the central role of emotions on identity formation. His main thesis is that fundamentalism must be understood as a process linked to identity and identification (not a thing) and that theories which take into account the crucial role of emotions, feelings, and the environment can explain fundamentalism, including Islamic fundamentalism, more accurately then social determinist and/or cultural constructivist theories can (pp. 77-80). The author thus sets out to “engage with an incredibly expanding academic literature [on Islamic fundamentalism] that tends to treat religious fundamentalism on the basis of culturalist or social theory discourse” (p. 153). He uses the same analytical lens adopted in his Jihad beyond Islam (London: Berg, 2006) ...